TO THE CONTACT PROBLEM AT THE STEADY STATE OF ROLLING - Ilman, V. M.; Razumov, S. Yu. (Science and Transport Progress, 2005)
With the help of example of plane contact problem for elastic bodies is demonstrated, that irregular rolling with homogeneous zone of adhesion and inhomogeneous contact zone with the help of Petrov-Fromm model is impossible.